Transcriptomic profile of the zoonotic parasite Anisakis pegreffii upon in vitro exposure to human dendritic cells - Palomba, Marialetizia; Rughetti, Aurelia; Castrignanò, Tiziana; Napoletano, Chiara; Roca-Geronès, Xavier; Pinna, Valentina; Liberati, Franco; Canestrelli, Daniele; Mattiucci, Simonetta (Frontiers in Cellular and Infection Microbiology, 2025)
Anisakis pegreffii is a zoonotic marine nematode whose life-cycle involves marine organisms–small crustaceans, fish and squids as intermediate/paratenic hosts, and marine mammals, mainly cetaceans–as definitive ones. When its third-stage larvae (L3) are accidentally ingested by humans with the consumption of raw or undercooked parasitized fish and/or squids, the parasite fails to complete its life cycle, leading to human anisakiasis. Despite increasing interest in understanding the molecular basis of pathogenic effects in human anisakiasis, the transcriptomic response of A. pegreffii L3 to interaction with human immune cells, remains poorly understood. Thus, in this study, the transcriptomic profile of A. pegreffii L3 larvae under in vitro exposure to human dendritic cells (DCs) was performed for the first time. A total of 3914 differentially expressed genes (DEGs) were identified in A. pegreffii L3 after exposure to immature DCs (iDCs), by RNA-seq, allowing to detect 1868 upregulated and 2046 downregulated transcripts. Upregulated genes were significantly enriched in pathways related to energy metabolism, oxidative stress response and structural maintenance, suggesting active metabolic and structural adaptation to immune-induced stress. Conversely, genes involved in cytoskeletal organization and intracellular trafficking were downregulated, potentially reflecting the parasite’s developmental arrest in an unsuitable host such as humans. These findings provide novel insights into the molecular response pathways activated by this zoonotic parasite during the early stages of interaction with the human immune system.